Relationship between CBC and ESR and duration of disease in patients with systemic lupus erythematosus (SLE) - Abira, Mahmuda; Akhter, Qazi Shamima (Journal of Bangladesh Society of Physiologist, 2018)
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease and is associated with considerable morbidity. Hematological abnormalities may be the initial manifestation. Duration may have impact on their hematological parameters. Objective: To observe the relationship of Complete Blood Count (CBC) and Erythrocyte sedimentation Rate(ESR) with duration of disease in patients with SLE. Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from July 2016 to June 2017. Total 60 subjects including both sexes were selected with age ranging from 18 to 55 years. Among them, 30 subjects with SLE were study group and 30 age matched healthy subjects were control group. Total count of RBC, WBC, Platelet and ESR were estimated by automated hematology analyzer. Statistical analysis was done by unpaired Students æt” test, Chi Square test and Pearson’s correlation coefficient (r) test. Results: In this study, ESR was significantly (p<0.001) higher and RBC,WBC and platelet counts were significantly (p<0.001) lower in SLE patients in comparison to that of control. On correlation analysis, RBC and WBC showed significant negative correlation with duration of disease in patients with SLE. Conclusion: This study concludes that CBC and ESR were altered in SLE patients and it was related to duration of disease. J Bangladesh Soc Physiol. 2018, December; 13(2): 41-46